Outcome of treatment of unstable intertrochanteric fractures using proximal femoral nail augmented with trochanteric stabilization plate - Rahman, K. Nafiz; Karim, M. Rezaul; Islam, M. Merajul; Alam, M. Shariful; Paramanik, M. Harun-or-Rashid; Kabir, Hasnan Zobayed; Mottalab, M. Abdul (International Journal of Research in Orthopaedics, 2025)
Background: Unstable intertrochanteric fractures remain a major challenge in the elderly population, often associated with high morbidity and complications. Proximal femoral nail (PFN) fixation provides stable internal fixation, while the addition of a trochanteric stabilization plate (TSP) is expected to enhance lateral wall support, reducing implant failure and improving outcomes. Methods: This prospective observational study was conducted at the National Institute of Traumatology and Orthopaedic Rehabilitation (NITOR), Dhaka and a private clinic, from July 2024 to March 2025. Thirty patients with unstable intertrochanteric fractures underwent fixation with PFN augmented by TSP. Demographic data, operative details, perioperative complications, radiological outcomes and functional results were recorded. Patients were followed up for six months and functional outcomes were assessed using the Harris hip score (HHS). Results: The mean age was 60.3±11.5 years, with males comprising 60% of patients. AO/OTA type 31-A2 fractures were the most common (63.3%). Mean operative time was 78±12 minutes, with minimal intraoperative complications. Radiological union occurred at a mean of 15.8±2.4 weeks. Implant-related complications were infrequent, with cut-out and back-out noted in 3.3% each. Early complications included superficial surgical site infection (3.3%) and deep vein thrombosis/pulmonary embolism (3.3%). Functional outcomes improved steadily, with the mean HHS rising from 42.3±6.1 at discharge to 88.2±6.7 at 6 months, indicating satisfactory hip function recovery. Conclusions: PFN augmented with TSP appears to be an effective fixation strategy for unstable intertrochanteric fractures, ensuring reliable fracture union, low complication rates and favorable functional outcomes.